Overview of energy storage systems in distribution networks: Placement, sizing, operation, and power quality. (August 2018) - Das, Choton K.; Bass, Octavian; Kothapalli, Ganesh; Mahmoud, Thair S.; Habibi, Daryoush
Abstract: The deployment of energy storage systems (ESSs) is a significant avenue for maximising the energy efficiency of a distribution network, and overall network performance can be enhanced by their optimal placement, sizing, and operation. An optimally sized and placed ESS can facilitate peak energy demand fulfilment, enhance the benefits from the integration of renewables and distributed energy sources, aid power quality management, and reduce distribution network expansion costs. This paper provides an overview of optimal ESS placement, sizing, and operation. It considers a range of grid scenarios, targeted performance objectives, applied strategies, ESS types, and advantages and limitations of the proposed systems and approaches. While batteries are widely used as ESSs in various applications, the detailed comparative analysis of ESS technical characteristics suggests that flywheel energy storage (FES) also warrants consideration in some distribution network scenarios. This research provides recommendations for related requirements or procedures, appropriate ESS selection, smart ESS charging and discharging, ESS sizing, placement and operation, and power quality issues. Furthermore, this study identifies future research opportunities in relation to challenges for optimal ESS placement planning, development and implementation issues, optimisation techniques, social impacts, and energy security. Abstract : Highlights: A comprehensive review of available energy storage systems (ESSs) is presented. Optimal ESS sizing, placement, and operation are studied. The power quality issues and their mitigation scopes with ESSs are discussed. Insights into decision-making tools: Analysing software & optimisation approaches. The challenges for ESS development and placement are identified.